The Role of Project Based Learning Strategies in Fiqih Subjects - Suhada, Karya; Mark, Elladdadi; Xavier, Embrechts; Margarida, Kruger; Intes, Amina (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The learning strategies commonly used by teachers are lecture, discussion and demonstration strategies. Even though there are many learning strategies, one of them is the Project Based Learning strategy. This strategy is very suitable for students' learning to deepen their knowledge and develop their abilities in carrying out activities. The purpose of this research is to determine the role of project-based Project Based Learning strategies in fiqh lessons. This research uses quantitative methods using survey models and in-depth interviews. The survey used in this research is online based. The results of this research show that students' understanding increases when the Project Based Learning strategy is applied by the teacher in the learning process. Conclusion pThis research explains that the role of the Project Based Learning strategy really helps teachers in the teaching and learning process in fiqh subjects. So that student achievement increases and student enthusiasm for learning increases. Therefore, the limitation of this research is that the researcher only conducted research on the role of Project Based Learning strategies in fiqh lessons. The researcher hopes that future researchers can conduct research on Project Based Learning strategies by developing this strategy in other subjects.